Carbon stock in the biomass of native urban fragments: A case study in an Atlantic Forest remnant in Brazil - Carla T. Pertille; Ernandes da Cunha-Neto; Carlos R. Sanquetta; Alexandre Behling; Ana P. Dalla-Corte (Forest Systems)
Aim of study: In the face of global concern about climate change, urban forests have great potential in the scenario of mitigating climate change and reducing emissions by carbon dioxide. Thus, the objective of this work was to evaluate the potential for carbon and carbon dioxide (CO2) removal of a forest fragment.